MAIT cells and the microbiome - Jabeen, Maisha F.; Hinks, Timothy S. C. (Frontiers in Immunology, 2023)
Mucosal associated invariant T (MAIT) cells are innate-like T lymphocytes, strikingly enriched at mucosal surfaces and characterized by a semi-invariant αβ T cell receptor (TCR) recognizing microbial derived intermediates of riboflavin synthesis presented by the MHC-Ib molecule MR1. At barrier sites MAIT cells occupy a prime position for interaction with commensal microorganisms, comprising the microbiota. The microbiota is a rich source of riboflavin derived antigens required in early life to promote intra-thymic MAIT cell development and sustain a life-long population of tissue resident cells. A symbiotic relationship is thought to be maintained in health whereby microbes promote maturation and homeostasis, and in turn MAIT cells can engage a TCR-dependent “tissue repair” program in the presence of commensal organisms conducive to sustaining barrier function and integrity of the microbial community. MAIT cell activation can be induced in a MR1-TCR dependent manner or through MR1-TCR independent mechanisms via pro-inflammatory cytokines interleukin (IL)-12/-15/-18 and type I interferon. MAIT cells provide immunity against bacterial, fungal and viral pathogens. However, MAIT cells may have deleterious effects through insufficient or exacerbated effector activity and have been implicated in autoimmune, inflammatory and allergic conditions in which microbial dysbiosis is a shared feature. In this review we summarize the current knowledge on the role of the microbiota in the development and maintenance of circulating and tissue resident MAIT cells. We also explore how microbial dysbiosis, alongside changes in intestinal permeability and imbalance between pro- and anti-inflammatory components of the immune response are together involved in the potential pathogenicity of MAIT cells. Whilst there have been significant improvements in our understanding of how the microbiota shapes MAIT cell function, human data are relatively lacking, and it remains unknown if MAIT cells can conversely influence the composition of the microbiota. We speculate whether, in a human population, differences in microbiomes might account for the heterogeneity observed in MAIT cell frequency across mucosal sites or between individuals, and response to therapies targeting T cells. Moreover, we speculate whether manipulation of the microbiota, or harnessing MAIT cell ligands within the gut or disease-specific sites could offer novel therapeutic strategies.